Code switching in Grade 11 students of UM Peñaplata College (ELT Forum: Journal of English Language Teaching, 2022)
This study aimed to discover the code switching found in impromptu speeches of the Grade 11 students of UM Peñaplata College. Specifically, the study sought to determine and describe the common words used in code switching in the impromptu speeches of the Grade 11 students and to analyze the types and functions of the common words they code switched. Since there have been no studies related to CS in the Island Garden City of Samal, the researchers are urged to conduct this kind of research. In addition to this, the researchers also want to know the role of CS in the academe since English language proficiency is highly necessary especially in an English classroom. The participants of this study are from UM Peñaplata College, specifically the Grade 11 Senior High School students. Among the 78 respondents, there were 67 purposively selected which were subjected to Textual Analysis. Analysis revealed four most common code-switching words committed in impromptu speeches. These are ahm, ah, kanang, and ay. The types of these code-switching words are intersentential, intra-sentential, intra-word, and tag-switching. Also, the functions of these code-switched words are fillers, hesitations, discourse markers, literary translation, and repetition of words. With these, language educators should continuously find strategies to suit the ever-changing nature of the curriculum and handle the weakness evident in the teaching of the English language.